2004
DOI: 10.1523/jneurosci.1991-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Afferent Glutamate Heterosynaptically Modulates GABA Release onto Second-Order Neurons via Distinctly Segregated Metabotropic Glutamate Receptors

Abstract: The balance between excitation and inhibition dictates central integration. Glutamatergic and GABAergic neurotransmission dominate this process. Cranial primary afferents enter the brainstem to release glutamate (Glu) onto second-order neurons within the caudal nucleus tractus solitarius (NTS) to initiate autonomic reflexes. The simplest pathways for these reflexes contain as few as two central neurons, but display robust frequency-dependent behavior. Within NTS, multiple metabotropic Glu receptors (mGluRs) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 40 publications
3
74
2
Order By: Relevance
“…Cranial visceral afferent excitation of second-order NTS neurons relies on non-NMDA receptor mediated glutamatergic transmission (Jin et al, 2004a;Jin et al, 2004b). Propofol did not alter the shape of EPSC events whether evoked or spontaneous, a result consistent with cortical neurons (Kitamura et al, 2003).…”
Section: Propofol Does Not Affect Glutamatergic Transmission In Seconsupporting
confidence: 62%
“…Cranial visceral afferent excitation of second-order NTS neurons relies on non-NMDA receptor mediated glutamatergic transmission (Jin et al, 2004a;Jin et al, 2004b). Propofol did not alter the shape of EPSC events whether evoked or spontaneous, a result consistent with cortical neurons (Kitamura et al, 2003).…”
Section: Propofol Does Not Affect Glutamatergic Transmission In Seconsupporting
confidence: 62%
“…Note that we examined only ionotropic receptors; the presence of GABA and glutamate metabotropic receptors in vagal brain stem circuits (17,21,35,38,47,48,60) adds another potentially larger level of complexity. Indeed, in the present study we did not examine the contribution of metabotropic receptors to the basal firing rate of DMV neurons and thus we cannot exclude their activation; however, we did not observe any significant effect on the DMV membrane induced by the GABA B antagonist saclofen (17) or Kynurenic acid was applied first, followed by bicuculline.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence from different laboratories, including our own, have shown that even within a relatively restricted group of nuclei, such as those comprised in the dorsal vagal complex, fundamental differences exists in the organization of synaptic circuits controlling GI, cardiovascular, and respiratory functions (1,3,6,14,15,17,18,24,29,45,51,52). This arrangement is quite logical, when considered from a physiological standpoint, since the requirements of each system vary greatly in the type, as well as the timing and duration, of responses.…”
Section: Discussionmentioning
confidence: 99%